Exploring DPT Students' Perceptions of Team Function in a Collaborative Integrated Clinical Education Experience. Issue 3 (2017) - Covington, Kyle; Myers, Katherine; Rodriguez, Jennifer
Abstract : Introduction. : Integrated clinical education (ICE), defined as clinical learning experiences embedded within the didactic portion of a DPT curriculum, is an integral component of an overall clinical education curriculum. The collaborative supervisory model has been applied to ICE experiences in DPT curricula. Two physical therapist (PT) education programs developed similar ICE experiences incorporating the collaborative model as a component of their clinical education curricula. Benefits for student learning have been described in the literature for both of these models—in isolation, but not combined. The purpose of this study was to determine factors that students felt contributed to successful team function in a collaborative ICE experience. Review of Literature. : ICE can provide opportunities for students to develop knowledge, skill, and professional behaviors in preparation for full‐time and final clinical experiences. There is a great deal of literature that supports the collaborative model of clinical education to facilitate teamwork and collaboration, deeper level of critical thinking and problem solving, and enhanced clinical competence. Despite the benefits of including ICE in a DPT curriculum, as well as the benefits of the collaborative model of clinical education, the physical therapy literature does not describe factors leading to successful team function when these 2 models of CE are combined. Methods and Subjects. : Subjects were 51 PT student teams (3 to 4 people each) from Duke University (2 cohorts) and the University of Colorado (1 cohort) who participated in a collaborative ICE experience. Following their first 2 weeks of ICE, student teams were instructed to create a mind map that depicted how their team functioned together in the clinic. Teams utilized an online mapping tool, "Coggle It, " to complete the mapping. The research team employed incident coding processes established in the literature to code the primary concepts of the team mind maps. Chi Square analysis was used to determine numeric differences across all codes among the 3 student team cohorts. Results. : Twenty‐four distinct codes were assigned to the primary concepts. Chi Square analysis revealed no significant differences between the 3 cohorts ( P > .01) across all codes. More than 50% of teams indicated that "group dynamics" and "team communication" were vital to the effective functioning of their team in the clinic. More than 25% of the teams included "individual student qualities, " "the learning environment, " "practicing skills, " "the instructor's teaching strategies, " "adult learner characteristics, " and the "clinical instructor" of key importance. From the data, 4 themes emerged as being important for effective collaborative learning in an ICE: The Team, the Clinical Environment, the Individual Student, and the Clinical Instructor. Discussion and Conclusion. : The 4 themes identified in this study contribute to the literature surrounding student learning in clinical education, specifically a collaborative ICE experience. This study suggests that these characteristics are important for positive experiences and should be factors that are considered by both academic programs and clinical instructors when designing, implementing, and teaching in a collaborative ICE experience.